VARIASI FORMULA PUMAKKAL TERHADAP KADAR N, P, K PADA PUPUK CAIR LIMBAH PRODUKSI MIE SEBAGAI PENDUKUNG BELAJAR BIOLOGI BERUPA LEMBAR KEGIATAN PESERTA DIDIK (LKPD) - Tasa Gandini; Agus Sutanto; Triana Asih (EDUBIOLOCK, 2022)
This study aimed to determine the variation of the pumakkal formula on the levels of N, P, K in the liquid fertilizer of noodle production waste, to determine the variation of the pumakkal formula according to the Indonesian National Standard (SNI) as a material for constructing support for learning biology. This type of research is an experimental study using the pumakkal formula P1 (3 bacteria), P2 (6 bacteria), P3 (9 bacteria), P4 (12 bacteria), and P5 (15 bacteria). The parameter observed was the content of Nitrogen (N) levels. Phosphorus (P), and Potassium (K). Analyzed using qualitative methods by comparing the results with the SNI for liquid fertilizers. Based on the results of the study, there was an effect of variations in the pumakkal formula on the liquid waste of noodle production. testing with SNI for liquid fertilizer showed that treatment 3 (P3) with a percentage yield of 2,092, treatment 4 (P4) with a result of 2,386, and treatment 5 (P5) with a result of 2,445 met SNI, and the best results were in treatment 5 (P5). Based on the validation analysis, learning support has a percentage value of 97.5%, so it is feasible to be used as a support for learning biology in the form of Student Activity Sheets (LKPD).